Case studies on art education in Egypt - Hamama, Mahitab (AUC Knowledge Fountain, 2014)
Art education, art class in particular, is not given as much attention as core subjects at schools in Egypt. The research examines two private language schools in Cairo and how they handle art education. It compares the teaching and viewpoints of art teachers at both schools as well as those of students. The research will address the following questions: (1) whether art education is neglected in private language schools in Egypt; and (2) if special attention is given to art education curriculum and teaching methods. This study is a qualitative one; data sources such as key informant interviews and document reviews are used to gather data about the art programs at the two private language schools. The study concludes that there are art programs at both schools studied; however, the teaching methods used are very limited. There is no diversity. Schools do not provide professional development for teachers, and the curriculum is not readily accessible for the teachers to teach. The study ends with several recommendations that could enhance the art programs in all Egyptian schools.